Campus Canopy, 1935-10-18 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1935)
Freshmen Will Seek Ancient Gray Hat in Annual Local Rite -- Journalism is Great Fun Indeed for those who Aren't Journalists -- Halliburton to Make Interesting Talk on his Foreign Travels -- English Club Holds Its Regular Meeting Monday -- Most Elective Officers Upon Campus Selected -- Carnival will Present Unusual Features Here -- Chapel Notice
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals